2017
DOI: 10.1183/23120541.00009-2017
|View full text |Cite
|
Sign up to set email alerts
|

EBUS-TBNA in PET-positive lymphadenopathies in treated cancer patients

Abstract: Mediastinal lymph node enlargement is common in the follow-up of patients with previously treated malignancies. The aim of this study is to assess the role of endobronchial ultrasound (EBUS) transbronchial needle aspiration (TBNA) for cyto-histological evaluation of positron emission tomography with 18fluorodeoxyglucose (PET) positive mediastinal and hilar lymph nodes developed in patients with previous malignancies.All EBUS-TBNA cases performed from January 2012 to May 2016 were retrospective reviewed. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Anthracosis has been reported to be another cause of false positivity on PET-CT, 9,18 and approximately 9% of PET-CTþ/ CytoÀ lymph nodes in our study had anthracotic pigmentladen macrophages described in the cytology report. We did not find any difference in the SUVs between aspirates containing lymphoid tissue with anthracotic pigment-laden macrophages versus just lymphoid tissue.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Anthracosis has been reported to be another cause of false positivity on PET-CT, 9,18 and approximately 9% of PET-CTþ/ CytoÀ lymph nodes in our study had anthracotic pigmentladen macrophages described in the cytology report. We did not find any difference in the SUVs between aspirates containing lymphoid tissue with anthracotic pigment-laden macrophages versus just lymphoid tissue.…”
Section: Discussionsupporting
confidence: 54%
“…5,6 Several studies have demonstrated the effectiveness of EBUS-TBNA for invasive nodal staging of lung cancer, for tissue sampling for mediastinal and lung tumors, and for the diagnosis of lymphoproliferative disorders. 2,[7][8][9][10] However, studies correlating EBUS-TBNA cytology with PET-CT findings are limited and are often small collections of cases. In this study, we compared the cytologic and clinical findings of PET-CTpositive/cytologically malignant (PET-CTþ/Cytoþ) versus PET-CT-positive/cytologically benign (PET-CTþ/CytoÀ) lymph nodes sampled by EBUS-TBNA in a large series of patients at a cancer center.…”
mentioning
confidence: 99%
“…Evaluation of MHLE and mediastinal masses in patient with known/suspected EPMs constitutes ~10%‐16% of all indications for which patients undergo EBUS‐TBNA . Metastases are identified in only 40%‐50% of these patients, of whom 5%‐23% patients are found to harbour a second primary malignancy, most commonly in the lung . A significant proportion (9%‐20%) have granulomatous diseases, further characterised as TB (2%‐9%) or sarcoidosis in few studies .…”
Section: Discussionmentioning
confidence: 99%
“…False‐negative EBUS‐TBNA results are not uncommon. In previous studies, patients with a negative EBUS‐TBNA result (reactive/granulomatous/inadequate) underwent mediastinoscopy/additional surgical biopsies or were kept on radiological follow‐up for 6‐18 months to look for progressive lymph node enlargement . Malignancy was eventually detected in 9‐27% of these patients and the NPV of EBUS‐TBNA for malignancy ranged from 73% to 92% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation